(untitled) (Alexandria, VA, 2003)
This book is intended for a professional audience, and the assumption is that students using this book have a prior knowledge of basic environmental engineering and fluid mechanics or hydraulics. Knowledge of calculus is helpful but is not essential. In the selection of topics and the presentation of the material, the objective is education as opposed to training. That is, the student is expected to emerge from using this book having not only a knowledge of the technology of wastewater treatment, but also a deeper understanding of the design process. The hope is that upon graduation from this course, the young engineer will be encouraged to always ask the "why" question and challenge the status quo. Wastewater Treatment Plant Design has a wealth of practical design information, as originally collected in the WEF Manual of Practice. Real life design experience is coupled with contemporary theory to produce a book that will have not only immediate value to students and practitioners, but will remain current and useful for years to come.
Keywords: Sewage disposal plants,Sewage,Sewage sludge,Thiết kế và xây dựng hệ thống cấp thoát nước,Cống thoát nước; Design and construction.,Purification